2013
DOI: 10.5578/mb.4208
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chlamydia trachomatis with Cell Culture, DFA and PCR Methods in the Genital Swab Samples of Symptomatic Patients

Abstract: Chlamydia trachomatis infection is considered the most prevalent bacterial sexually transmitted disease worldwide. C.trachomatis causes eye infections such as trachoma and newborn inclusion conjunctivitis, newborn pneumonia, genitourinary system infections and suppurative inguinal lymphadenitis namely lymphogranuloma venerum. The aim of this study was to investigate C.trachomatis by direct fluorescent antibody (DFA), polymerase chain reaction (PCR) and cell culture methods in the clinical samples sent to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…We also showed that DIF has well balanced ratio of sensitivity and specificity, but extremely low positive predictive value, which is the main reason why this test cannot be recommended for the diagnosis of an acute chlamydial infection. Similar values of DIF sensitivity and specificity are also presented in other studies [13,[26][27][28]. However, opposite to our findings, some of these earlier studies recommend DIF method as practical and inexpensive, relevant in routine laboratory practice and suitable for the early detection of infection because of its high sensitivity [26,27].…”
Section: Discussionsupporting
confidence: 72%
“…We also showed that DIF has well balanced ratio of sensitivity and specificity, but extremely low positive predictive value, which is the main reason why this test cannot be recommended for the diagnosis of an acute chlamydial infection. Similar values of DIF sensitivity and specificity are also presented in other studies [13,[26][27][28]. However, opposite to our findings, some of these earlier studies recommend DIF method as practical and inexpensive, relevant in routine laboratory practice and suitable for the early detection of infection because of its high sensitivity [26,27].…”
Section: Discussionsupporting
confidence: 72%
“…According to the mentioned effects of genital diseases, prevention, screening, and treatment are extremely important. The C. trachomatis is able to grow in cell culture, which is time‐consuming and costly . Moreover, M. hominis culture which is considered as gold standard method in clinical laboratory, is time‐consuming, requires live organism, and may yield ambiguous results .…”
Section: Discussionmentioning
confidence: 99%
“…The C. trachomatis is able to grow in cell culture, which is time-consuming and costly. 19,20,32 Moreover, M. hominis culture which is considered as gold standard method in clinical laboratory, is time-consuming, requires live organism, and may yield ambiguous results. 4 Molecular methods can be a useful tool to detect these two bacte- In a study by Aguilera-Arreola et al 35 successfully developed by designing specific primer and analysis of melting curves.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations